Teknik Pembuatan Visual Bulu Elang Jawa dalam Karya Body Painting Fantasi Berbasis Mixed Media - Alfina Najmul Falakh; Trisnani Widowati; Novia Restu Windayani (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
This study aims to explain the technique of creating visual depictions of Javan Hawk-eagle feathers in a mixed-media fantasy body painting and to evaluate the visual quality of the resulting feather textures in representing the morphological characteristics of the Javan Hawk-eagle, an Indonesian endemic animal. This study employed a descriptive qualitative method with descriptive percentage analysis. Data were obtained through an assessment process by three expert validators who evaluated the works based on indicators of elements and principles of fine art, the use of the body as a medium for aesthetic expression, creativity in beauty products, and aesthetic aspects in the beauty industry. Furthermore, percentage analysis was used to determine the visual quality of the works based on the validators' assessments. The results showed that the works obtained an average percentage of 96.7%, categorized as